Pengaruh Faktor Stimulus Ekspor dan Karakteristik Lingkungan Perusahaan terhadap Strategi Pemasaran Ekspor Serta Dampaknya pada Pencapaian Ekspor Batik di Eks Karesidenan Surakarta - Darmansyah -; Djumilah Zain; Armanu Thoyib; Candra Fajri Ananda (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study analyzes some factors that influence batik export performance in ex district surakarta. The Researcher links the export stimulus and environmental characteristic toward export marketing strategy and also to the impact of export stimulus, environmental characteristic and export marketing strategy on export performance. The purpose of this study is to explain the relationship between export stimulus and environmental characteristic toward the export marketing strategy. This study is also aiming at explaining about the relation of the export stimulus, the environmental characteristic and export marketing strategy toward export performance of Batik Company. The location of this study was in Ex-district of Surakarta. The total samples of this research were 108 companies but only 104 companies which could be investigated. The significant finding of this study is that the aid of market information from domestic/local government and importer and their political stability (environmental aspect) will improve the export performance. The strong willingness of the company managers to exploit the existing resources owned by the companies will support the export performance (impulse factor).Keywords: Export Stimulus, Environmental Characteristics, export marketing Strategy, export performance.